Perception and pursuit of entrepreneurial opportunities: an evolutionary economics perspective - Guido Buenstorf (Max Planck Institute of Economics, 2006)
Considerable debate surrounds the concept of entrepreneurial opportunities. This paper contributes to the discussion by bringing in concepts and findings from evolutionary economics. It makes three points. First, adopting an evolutionary market process perspective sheds new light on the nature of opportunities. Second, not only the pursuit of entrepreneurial opportunities, but also the further development of the entrepreneurial venture is dependent on subjective opportunity perception and interpretation. Third, findings on industry evolution help understand how opportunities, as well as agents' ability and willingness to pursue them, change over time. Effects of pre-entry experience on opportunity recognition and firm performance are also discussed.
Keywords: B25; D21; M13; L10; 330; opportunities; market process; business conceptions; industry evolution; spin-offs